THE SPIRITUAL AND CULTURAL SYMBOLS IN A MAHAYANA BUDDHIST TEMPLE ‘VIHARA LOTUS’ SURAKARTA - Lery Prasetyo (Analisa: Journal of Social Science and Religion, 2019)
The symbols contained in a vihara is intentionally used to remind the people to something that is believed, both cultural and spiritual values. This article aims to analyze the meaning and value of spiritual and cultural symbols in Vihara Lotus Surakarta. This is a qualitative research. This article shows that (1) The meaning and value of spiritual symbols in Vihara Lotus can be found on the category of altar and statue which consist of ancestor altar, Amitabha Buddha Altar, Avalokitesvara Altar, Three Buddhas Alta, Si Mien Fo Altar, Maitreya Buddha, Si Da Tian Wang Statues, And Earth Gods. Then in category of Prayer tools consist of Ching/Gong, Muk Ie, He Che, and Tan Che. Those spiritual symbols have meaning and value in term of the Buddha teaching such as the Sigalovada sutta, sukhavati realm, reflection of Buddhas nature, concept of Tri Kaya, affection state, four nobles qualities, dharma wheel turning, awareness, equanimity concept, introspection, and catumaharajika realm. (2) Meaning and Value of Cultural Symbols in Vihara Lotus can be found on the category of altar and statue consists of Thian Kong Altar, Chinese Generals, Earth gods, and Horse statues. Then in plant and food category consist of soy bean, Candy and Cookie, cigarette, wine, Chinese evergreen, and pineapple. Those cultural symbols have meaning and value in term of Chinese tradition and habit, such as Tradition of Sky Praising, merits appreciation, Chinese mythology, traditional food, hope of better life, special service to idol, and hope of sustenance.